Counter-Non-Anti-Remembrance. The Anti-monumental Practices by TIST Collective - Yulia S. Tikhomirova (European Journal of Creative Practices in Cities and Landscapes)
In the recent decades, monumentality has been significantly reconsidered with its symbolic materiality and agency in public spaces. Counter-, non-, and anti-monumental practices have emerged on the scene of contemporary art as a new, critical mode of commemorative and social ritual. While addressing the well-known query on whether monumentality can still be considered a valid tool able to synthesize and keep the collective memory, the current paper investigates the remembrance practices by TIST collective (Italy). In the last two years TIST implemented a series of artistic actions in the urban space designed to address the emergence and endurance of a commemorative community and the possibility of remembrance as a public ritual.